Peranan Baitul Mal Wat Tamwil Terhadap Perekonomian Sumatera Utara - Rini Hayati Lubis (AL-MASHARIF: JURNAL ILMU EKONOMI DAN KEISLAMAN, 2015)
Years 2014-2015 the number of poor people increased by 1.46367 millioninhabitants, especially in rural areas in the province of North Sumatra is thenumber one cause of unemployment increases, and therefore the necessary role ofBaitul Mal Wat Tamwil (BMT) to the economy of North Sumatra especially ruralcommunitiesBMT role towards improving the economy of North Sumatera give apositive thing that the development and financing of small businesses, helping tobreak the dependence on moneylenders, maintaining economic justice communitywith equitable distribution and makes the society to be able to apply sharia-basedeconomy